A Clinical Study of Lens Induced Glaucoma - Dr. Beatrice Choppara, Dr. Ch. Srinivasa Murty Dr. V. Murali Krishna , (International Journal of Scientific Research and Management (IJSRM), 2015)
: Glaucoma is one of the major causes of blindness in our country. Like many other glaucoma the management of LENS INDUCED GLAUCOMA Is also challenging because earlier surgical management will make the difference in the final visual acuity and prognosis.